Comparison of the Novel Oral Anticoagulants Apixaban, Dabigatran, Edoxaban, and Rivaroxaban in the Initial and Long-Term Treatment and Prevention of Venous Thromboembolism: Systematic Review and Network Meta-Analysis. - A T Cohen; M Hamilton; S A Mitchell; H Phatak; X Liu; A Bird; D Tushabe; S Batson (PLoS ONE)
Background Anticoagulation with low molecular weight heparin and vitamin K antagonists is the current standard of care (SOC) for venous thromboembolism (VTE) treatment and prevention. Although novel oral anti-coagulants (NOACs) have been compared with SOC in this indication, no head-to-head randomised controlled trials (RCTs) have directly compared NOACs. A systematic review and network meta-analysis (NMA) were conducted to compare the efficacy and safety of NOACs for the initial and long-term treatment of VTE. Methods Electronic databases (accessed July 2014) were systematically searched to identify RCTs evaluating apixaban, dabigatran, edoxaban, and rivaroxaban versus SOC. Eligible patients included adults with an objectively confirmed deep vein thrombosis (DVT), pulmonary embolism (PE) or both. A fixed-effect Bayesian NMA was conducted for outcomes of interest, and results were presented as relative risks (RR) and 95% credible intervals (Crl). Results Six Phase III RCTs met criteria for inclusion: apixaban (one RCT; n = 5,395); rivaroxaban (two RCTs; n = 3,423/4,832); dabigatran (two RCTs; n = 2,539/2,568); edoxaban (one RCT; n = 8,240). There were no statistically significant differences between the NOACs with regard to the risk of 'VTE and VTE-related death. Apixaban treatment was associated with the most favourable safety profile of the NOACs, showing a statistically significantly reduced risk of 'major or clinically relevant non-major (CRNM) bleed' compared with rivaroxaban (0.47 [0.36, 0.61]), dabigatran (0.69 [0.51, 0.94]), and edoxaban (0.54 [0.41, 0.69]). Dabigatran was also associated with a significantly lower risk of 'major or CRNM bleed' compared with rivaroxaban (0.68 [0.53, 0.87]) and edoxaban (0.77 [0.60, 0.99]). Conclusions Indirect comparisons showed statistically similar reductions in the risk of 'VTE or VTE-related death for all NOACs. In contrast, reductions in 'major or CRNM bleed' for initial/long-term treatment were significantly better with apixaban compared with all other NOACs, and with dabigatran compared with rivaroxaban and edoxaban. Results from the current analysis indicate that the NOACs offer clinical benefit over conventional therapy while highlighting relative differences in their bleeding profile.